Influence of Irrigation on Lysimeter-grown Sage (Salvia Officinalis L.) - Valkovszki, Noémi Júlia; Székely, Árpád; Szalóki, Tímea; Kun, Ágnes; Kolozsvári, Ildikó; Tavaszi-Sárosi, Szilvia; Jancsó, Mihály (Journal of Central European Green Innovation, 2022)
The sage is one of the most widely applied herbs. It is used equally by the pharmaceutical, cosmetic and food industries. The essential oil content and composition of sage, i.e. the drug quality, are significantly influenced by the growth conditions (soil, nutrient, water and light supply). The medicinal sage is known as a drought-tolerant plant. However, the low rainfall weather of recent years in Hungary highlighted the importance of investigation of irrigation’s effect to achieve optimal drug yield and quality. In our experiment, we studied the effect of irrigation on Salvia officinalis L. grown at the largest lysimeter station in Central Europe. In the two-year experiment, the plant height, plant diameter, shoot length, SPAD value, as well as the biomass, fresh and dry leaf weight; the essential oil content and composition of 16 plants per treatment were evaluated under rainfed and irrigated (105 mm Körös oxbow lake water) conditions. Results showed that the irrigation caused a significant increase in plant height, plant diameter, shoot length, and yield (total biomass: unirrigated: 470.46 g plant-1; irrigated: 827,48 g plant-1) in both experimental years. The irrigation caused an increase in essential oil content. The main components in the essential oil were α-Thujone, Camphor, 1,8-Cineol, β-Thujone, and Camphene; while the amount of Ledole in 2021 and the Viridiflorole in 2022 was more than 6%. By the influence of irrigation, the SPAD value and Trans-Sabinyl-acetate were decreased.